2007
DOI: 10.1021/jp071101n
|View full text |Cite
|
Sign up to set email alerts
|

A Calorimetry and Light Scattering Study of the Formation and Shape Transition of Mixed Micelles of EO20PO68EO20Triblock Copolymer (P123) and Nonionic Surfactant (C12EO6)

Abstract: The interaction between the nonionic surfactant C12EO6 and the poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) triblock copolymer EO20PO68EO20 (P123) has been investigated by means of isothermal titration and differential scanning calorimetry (DSC) as well as static and dynamic light scattering (SLS and DLS). P123 self-assembles in water into spherical micelles at ambient temperatures. At raised temperatures, the DSC data revealed a sphere-to-rod transition of the P123 micelles around 60 degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
58
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 55 publications
7
58
0
1
Order By: Relevance
“…In addition, the raw calorimetric curves, also shown as inset in Figure 3, indicated that, around this special molar ratio, the peaks were composed by a fast endothermic and a slow exothermic process, taking around 15-20 min to equilibrate. The same time dependence was observed for structural measurements using light and small-angle X-ray scattering techniques [13].…”
supporting
confidence: 54%
“…In addition, the raw calorimetric curves, also shown as inset in Figure 3, indicated that, around this special molar ratio, the peaks were composed by a fast endothermic and a slow exothermic process, taking around 15-20 min to equilibrate. The same time dependence was observed for structural measurements using light and small-angle X-ray scattering techniques [13].…”
supporting
confidence: 54%
“…Thus, although nonionic surfactants are generally known not to interact with nonionic polymers, some articles describe strong interactions taking place in specific systems constituted by C 12 EO 6 and a wide range of Pluronics [22][23][24]. The C 12 EO 6 structure is quite similar to Rewopal X1207L and this synergistic behavior may be extrapolated to our system.…”
Section: Association Of Pluronic P123 With Rewopal X1207lmentioning
confidence: 75%
“…The presence of this composite peak is attributed to the formation of vesicles or a dispersion of a lamellar liquid crystal in a two-step process [57]. It is known that the enthalpy change of pure L121 solutions is related with the aggregation process, and results from the dehydration of PPO chains [57]. Below a certain temperature (i.e.…”
Section: Dsc Measurementsmentioning
confidence: 99%
“…Actually, the formation of micelles in other Pluronic aqueous solutions is reflected by a single peak, as in the present case when AOT is added. In L121 + sodium dodecyl sulfate (SDS) mixed systems, the micellization enthalpy also decreases upon adding the ionic surfactant, but the onset temperature actually increases [57]. AOT is much less hydrophilic than SDS, and therefore the effect should be different.…”
Section: Dsc Measurementsmentioning
confidence: 99%